Revision of Neobertiera (Rubiaceae, Sipaneeae) with observations on distyly, and three new species from the Guianas - Delprete, Piero G. (Phytotaxa, 2015)
The ongoing treatments for the Flora of the Guianas (Guyana, Surinam, and French Guiana) and the monographic study of the tribe Sipaneeae prompted a revision of Neobertiera, discovering the distylous condition of this genus, and three undescribed species, one probably restricted to Guyana, and two probably restricted to French Guiana. Because of these novel observations and the different kinds of inflorescence of the newly described species, a generic description, with yet another amendment, a key to the species, illustrations, and material examined are presented.